A new vaccination regimen using adenovirus-vectored vaccine confers effective protection against African swine fever virus in swine - Wenming Liu; Hengchun Li; Bo Liu; Tianxing Lv; Chenchen Yang; Si Chen; Liqiang Feng; Liangxue Lai; Ziyuan Duan; Xinwen Chen; Pingchao Li; Suhua Guan; et al. (Emerging Microbes and Infections, 2023)
African swine fever (ASF) is an acute and highly contagious lethal infectious disease in swine that severely threatens the global pig industry. At present, a safe and efficacious vaccine is urgently required to prevent and control the disease. In this study, we evaluated the safety and immunogenicity of replication-incompetent type-2 adenoviruses carrying African swine fever virus (ASFV) antigens, namely CP204L (p30), E183L (p54), EP402R (CD2v), B646L (p72), and B602L (p72 chaperone). A vaccine cocktail delivered by simultaneous intramuscular (IM) and intranasal (IN) administration robustly elicited both systemic and mucosal immune responses against AFSV in mice and swine and provided highly effective protection against the circulating ASFV strain in farmed pigs. This multi-antigen cocktail vaccine was well tolerated in the vaccinated animals. No significant interference among antigens was observed. The combined IM and IN vaccination using this adenovirus-vectored antigen cocktail vaccine warrants further evaluation for providing safe and effective protection against ASFV infection and transmission.